How to use global positioning systems (GPS) data to monitor training load in the "real world" of elite soccer - Ravé, G.; Granacher, U.; Boullosa, D.; Hackney, A. C.; Zouhal, H. (Frontiers in Physiology, 2020)
Modern physical training in elite sport is characterized by the systematic and continuous assessment of data on competitive and training performances (Clemente et al., 2019a). In team sports, Global Positioning Systems (GPS) technology is probably the most used monitoring tool to record workloads during training and competitions (Akenhead and Nassis, 2016).